Kirche und Zivilgesellschaft – Reformatorische Impulse und Gestaltungsaufga-be der Kirchen in Europa - Sándor FAZAKAS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Church and Civil Society – Impulses of Reformed Theology and the Role of the Churches in Shaping Europe. This contribution seeks to answer the role religions and churches, especially the Reformed churches, could play in developing and consolidating civil society and democracy. This study will examine the role of the Church in the Central and Eastern European social and political contexts. Therefore, we will first make an overview of the specifics of this phenomenon in the context of the region's recent history. Then we will look for the normative and substantive meanings of the term for the present going beyond its contextual definition. Finally, we will take note of the impulses of Reformed theology that can contribute to the strengthening of civil society and democratic culture. Will we do this in the context of the particular approach of Reformed theology, in the theological context of the threefold offices (triplex munus) of Christ. The Church, which shares in the royal, priestly and prophetic offices of Christ, shall assume special responsibilities in the life of the society following the threefold ministry of his Lord. In social and diaconal service, the Church must offer new, innovative solutions that promote quality of life (royal office) by working for a culture of reconciliation and compassion. The Church can move from the interior life of piety into the social sphere (priestly office), and through self-criticism and sober social critique, it can advocate for those most disadvantaged by political, economic and social processes (prophetic office). This paper is an edited version of a presentation given at the 2018 German-Hungarian Reformed Theological Conference in Soest, Westphalia. The author attended this conference with an esteemed colleague Béla S. Visky, and now dedicates this paper to him with much appreciation and love on his 60th birthday.